Active layer modification of commercial nanofiltration membrane using CuBTC/PVA matrix for improved surface and separation characteristics. Issue 21 (22nd January 2021) - Sharma, Uttkarshni; Shalini, Shweta; Basu, Subhankar; Saravanan, Pichiah; Jang, Min
Abstract: The present study proposes a facile route for the modification of commercial nanofiltration (NF) polymeric membrane by embedding metal organic framework (MOF) via dip coating. A mixed membrane matrix comprising of copper benzene‐1, 3, 5‐tricarboxylate (CuBTC) and polyvinyl alcohol (PVA) served as the new active layer. The obtained topography, functional group, and surface elemental analysis elucidated the presence of heterogeneous phase and the distribution of the MOF on the membrane. The dip coating well supported the modification through excellent adhesion. The water wettability of the modified membrane displayed a positive correlation with CuBTC loading in the PVA polymer matrix. Permeation and separation characteristics of the resultant membranes were investigated by retaining protein and carbohydrates from synthetic dairy wastewater (SDWW). The permeability rate of modified samples increased to 43% as compared to the commercial NF membrane. A significant improvement in the rejection rate of carbohydrate from 61% to 87% and protein from 88% to 94% was achieved. Membrane Fouling was found to be much lesser for the modified samples. The study highlights the potential of CuBTC as filler material for enhancing the separation characteristic of established NF membrane. Abstract :